Analisis Tingkat Kepatuhan Syariah Pada Bank Central Asia Syariah (BCAS) - Utama, Indra; Andiansyah, Farma; Jamaris, Edi (IJMA (Indonesian Journal of Management and Accounting), 2023)
This study aims to determine the level of sharia compliance of Bank BCA Syariah through their level of compliance with disclosure obligations ranging from disclosure of duties and responsibilities of the Sharia Supervisory Board (DPS), Disclosure of Financing Products such as Mudharabah, Murabahah, Musyarakah, Ijarah, Istisna and disclosure in Virtue Fund (Qard) and Zakat funds. This research uses a descriptive qualitative approach. The results of this study indicate that overall BCA Syaraiah has fulfilled the principle of compliance based on the 2019 annual disclosure report. This is because the disclosure of the duties and functions of the BCA Syariah Supervisory Board has been presented in accordance with applicable laws and regulations. In addition, the components of the disclosure of Islamic bank financing products as a whole are quite good by meeting the disclosure standards in accordance with the Sharia Banking Accounting Guidelines, but there are only a few disclosure components that have not been completed, especially in the disclosure report of Qard funds, Zakat and Istisna financing.